Pengaruh Konsentrasi Perekat Tapioka Pada Pembuatan Biobriket Dari Lumpur IPAL Produksi Minyak Sawit Dan Cangkang Biji Karet - Refvi Gusvita Sari; Elvi Yenie; Syarfi Daud (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
The use of fossil fuels is increasing every year, necessitating finding alternative energy sources as a substitute for fossil fuels. Alternative energy sources that can be used as renewable energy are biobriquettes derived from biomass. A very abundant agricultural waste, such as WWTP sludge, palm kernel shell production, but not utilized optimally. The purpose of this study was to study the effect of variations in tapioca adhesive concentration in the manufacture of biobriquette on the analysis of proximate and compressive strength produced. The process of making biobriquette in this study with variations changed the concentration of tapioca adhesive 5%, 8% and 11%. Fixed variations used were carbonization temperature of 300oC mud, 500oC rubber seed shells for 1 hour, raw material composition of WWTP sludge charcoal and 60%: 40% of the total weight of 10 gram briquettes and pressing pressure of 100 kg/cm2. Carbonization is carried out using furnaces and drying is carried out in a room 24 hours and then oven for 1 hour at a temperature of 105oC. The results showed that the best briquettes lie in the variation of 11% adhesive concentration which produces a compressive strength of 11,55 kg/cm2, moisture content of 7,5%, ash content of 7%, volatile content of 10,50% and carbon content of 75%.Keywords: biobriquette, rubber seed shell, carbonization, waste WWTP palm oil production, compressive strength.